THE THEORY OF EPISTEMOLOGICAL DIVERSITY AND SOME STRATEGIC GUIDELINES FOR HIGHER EDUCATION - Natalya I. Martishina (Высшее образование в России)
The theory of epistemological diversity is one of the modern trends in epistemology. Basing on this theory, the author gives a description of a special kind of knowledge - subject-practical knowledge. On author"s opinion the education system works both with scientific and subject-practical knowledge and it leads to a strategic contradiction because treatment of two different types of knowledge cannot be effectively implemented in standardized forms. The paper discusses the changes in the educational strategy required by a situation of coexistence of the two types of knowledge in higher education.